Guanidine salt / imidazole derivative-based composite proton exchange membrane for high-temperature fuel cell and preparation method of guanidine salt / imidazole derivative-based composite proton exchange membrane

By introducing a composite structure of fluorine-containing polybenzimidazole and guanidine salt/imidazole derivatives in the high-temperature proton exchange membrane, the problems of low conductivity and poor stability of the existing high-temperature proton exchange membrane are solved, and higher proton conductivity is achieved Rate and stability are suitable for high-temperature fuel cells.

CN119481185APending Publication Date: 2025-02-18CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733192.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing high-temperature proton exchange membrane has low conductivity and poor stability, which limits its practical application in fuel cells.

Method used

A composite proton exchange membrane of fluorine-containing polybenzimidazole (6FPBI) and guanidine salt/imidazole derivative (GBIM) was prepared by prepolymerization and high-temperature condensation polymerization, and GBIM was incorporated into 6FPBI as a filler to form 6FPBI-X Composite film.

Benefits of technology

It improves the proton conductivity and phosphoric acid fixation ability of the high-temperature proton exchange membrane, enhances the mechanical strength and stability of the membrane, and is suitable for high-temperature fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481185A_ABST
    Figure CN119481185A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer electrolyte membranes, and particularly relates to a guanidine salt / imidazole derivative-based composite proton exchange membrane for a high-temperature fuel cell and a preparation method. The preparation method comprises the following steps: firstly synthesizing fluorine-containing polybenzimidazole (6FPBI), then synthesizing a guanidine salt derivative (GBIM) containing imidazole and guanidyl, and finally preparing the guanidine salt / imidazole derivative filler polybenzimidazole composite proton exchange membrane. GBIM is a guanidyl imidazole derivative and has a stronger resonance effect, namely higher stability, and guanidyl and imidazole both have strong alkali properties, so that doping of phosphoric acid is facilitated; the composite membrane is prepared by adding the composite membrane as a filler into a polymer matrix, so that the phosphoric acid retention rate, the chemical stability, the proton conductivity and the high-temperature fuel cell performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer electrolyte membranes, and in particular relates to a composite proton exchange membrane based on guanidinium salt / imidazole derivatives for high-temperature fuel cells and a preparation method thereof. Background Art

[0002] As energy and environmental issues intensify, fuel cells with high conversion efficiency and environmental protection characteristics are becoming more and more popular. PEM is a key component of fuel cells, and PBI is considered to be the HT-PEM material with the most development potential. However, the proton conductivity of PBI itself is negligible, so it needs to rely on phosphoric acid to provide proton acceptors and donors. According to the Grotthuss mechanism, the degree of phosphoric acid doping will affect the density of the hydrogen bond network in the system and directly affect the proton conductivity of the PBI membrane.

[0003] In the research of PA / PBI membranes, how to ensure the mechanical strength of the membrane after doping without losing the phosphoric acid doping ability of the PBI membrane has always been the focus of research. Cross-linking is considered to be the best method to improve the plasticization effect, but the cross-linking structure will affect the doping of phosphoric acid. This influence mainly comes from two aspects. First, cross-linking will increase the complexity between the main chains and occupy space. Second, cross-linking will consume a large amount of -NH- bonds on the imidazole ring, which will lead to a reduction in the number of bonded phosphoric acid. The introduction of functional groups or structures will have a significant impact on the performance of PA / PBI membranes.

[0004] Quaternary guanidine cations have highly stable charge delocalization and have shown remarkable effects on improving the electrochemical properties of PA / PBI membranes. The resonance characteristics of the guanidine moiety can further enhance the resonance effect of imidazole, that is, the cations derived from guanidinoimidazole (a new type of quaternary ammonium reagent, including guanidine and imidazole) will have a stronger resonance effect than these two single cations, which means higher stability. Both guanidine and imidazole have strong alkaline properties that are conducive to the doping of phosphoric acid, which undoubtedly provides another idea for the application of guanidine salts in HT-PEM. However, the low conductivity and poor stability of high-temperature proton exchange membranes are still the main reasons limiting the practical application of high-temperature proton exchange membranes. Although the existing high-temperature proton exchange membranes that introduce a single guanidine or imidazole cation can improve the proton conductivity, the stability is still not well improved. Summary of the invention

[0005] The present invention uses 2,2-bis(4-carboxyphenyl)hexafluoropropane (6FDA) containing a flexible group and synthesizes fluorinated PBI (6FPBI) through prepolymerization and high-temperature polycondensation. Then, the benzimidazole part is introduced into the pentasubstituted guanidine through the Menschutkin reaction to obtain a guanidine salt derivative (GBIM) containing imidazole and guanidine groups. Finally, GBIM is added as a filler into 6FPBI to prepare a proton exchange composite membrane 6FPBI-X. The preparation steps of the high-temperature proton exchange membrane are as follows:

[0006] (1) Preparation of fluorinated polybenzimidazole (6FPBI)

[0007] Under nitrogen atmosphere, 3,3'-diaminobenzidine (DAB) and 4,4'-dicarboxy diphenyl ether (OBBA) were completely dissolved in polyphosphoric acid (PPA), heated to 180°C for 3 hours, then cooled to 140°C and 6FDA was added until completely dissolved, and heated to 180°C again for 3 hours (the molar ratio of DAB:OBBA:6FDA was 1:0.5:0.5). After the reaction, the solution was poured into deionized water for cooling, and the obtained solid was washed with deionized water several times and neutralized with NaHCO3 (PH=7). Finally, the product was placed in an oven for drying, and the obtained polymer was named 6FPBI.

[0008] (2) Preparation of bromobenzimidazole-containing small molecules (2BIM-2Br)

[0009] DAB and bromoacetic acid were added to HCl (5M) solution and refluxed for 6 hours under nitrogen atmosphere. After the reaction, the residual solid was removed by filtration, and the remaining solution was poured into an appropriate amount of deionized ice water. The solution was neutralized with NaHCO3 (adjusted to pH=7), and solids gradually precipitated as the acidity of the solution decreased. The obtained solid was washed with deionized water, filtered, and dried in an oven to obtain 2BIM-2Br.

[0010] The molar ratio of DAB to bromoacetic acid was 1:2.2.

[0011] (3) Preparation of pentasubstituted guanidine compound (BuTMG)

[0012] Under nitrogen atmosphere, 1,1,3,3'-tetramethylguanidine (TMG) was dissolved in acetonitrile, and then n-butyl bromide was slowly dripped into the solution under ice bath conditions. After the dropwise addition was completed, the ice bath was removed and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, a NaOH aqueous solution (20wt%) was slowly dripped into the flask under ice bath conditions, and then extracted with dichloromethane. After drying, dichloromethane was removed by rotary evaporation to obtain BuTMG, which was finally dried in a vacuum oven.

[0013] The molar ratio of TMG to n-butyl bromide is 1:1.1.

[0014] (4) Preparation of guanidine salt / imidazole derivatives (GBIM)

[0015] 2BIM-2Br and BuTMG (molar ratio of 1:1-2.2) were dissolved in DMSO. Then the mixture was reacted at 50°C for 24 hours, and ether was added dropwise to the solution to precipitate solid. Finally, the solid GBIM was dried in a vacuum oven. The structural formula of GBIM is shown below:

[0016]

[0017] (5) Preparation of 6FPBI-X composite membrane and phosphoric acid doping

[0018] 6FPBI and GBIM were dissolved in DMSO, respectively, and then the two solutions were mixed and ultrasonically treated for 4 hours. The homogenous mixed solution was cast on a glass plate, and the 6FPBI-X film was dried at 80°C. Where X is the amount of GBIM, and X in this patent is 1%, 3%, and 5%. The film sample was immersed in 85wt% phosphoric acid at 80°C for 12 hours to obtain a phosphoric acid-doped film.

[0019] The composite proton exchange membrane based on guanidine salt / imidazole derivatives prepared by the present invention can be used for high-temperature proton exchange membranes of hydrogen fuel cells.

[0020] The present invention has the following advantages:

[0021] (1) GBIM combines guanidine and imidazole to form a cation, which will have a stronger resonance effect and greater stability;

[0022] (2) GBIM has both guanidine and imidazole, both of which have strong alkaline properties and are more conducive to the doping of phosphoric acid;

[0023] (3) Introducing GBIM as a filler into the polymer will not reduce the NH bonds on the imidazole ring, but will also form a relatively strong acid-base interaction with the polymer main chain, providing a proton transfer channel to improve proton conductivity and enhance the phosphate fixation capacity;

[0024] (4) The composite film preparation process is simple and has good film-forming performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 for BuTMG (a), 2BIM-2Br (b) and GBIM (c) 1 HNMR spectrum. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments.

[0027] Example 1

[0028] Under nitrogen atmosphere, 1.07g DAB and 0.65g OBBA were completely dissolved in 20g PPA, heated to 180°C for 3 hours, then cooled to 140°C and 0.98g 6FDA was added until completely dissolved, and heated to 180°C again for 3 hours. After the reaction, the solution was poured into deionized water for cooling, and the obtained solid was washed three times with deionized water and neutralized with NaHCO3 (PH=7). Finally, the product was placed in an oven for drying, and the obtained polymer was named 6FPBI.

[0029] 1.07 g DAB and 0.76 g bromoacetic acid were added to 40 ml HCl (5 M) solution and refluxed for 6 hours under nitrogen atmosphere. After the reaction, the residual solid was removed by filtration, and the remaining solution was poured into 200 ml deionized ice water. The solution was neutralized with NaHCO3 (adjusted to pH = 7), and solids gradually precipitated as the acidity of the solution decreased. The obtained solid was washed with deionized water, filtered and dried in an oven to obtain 2BIM-2Br.

[0030] Under nitrogen atmosphere, 1.15g TMG was dissolved in 50ml acetonitrile, and then 1.51g n-butyl bromide was slowly dripped into the solution under ice bath condition. After the dropwise addition was completed, the ice bath was removed and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, 100ml NaOH aqueous solution (20wt%) was slowly dripped into the flask under ice bath condition, and then extracted with dichloromethane, dried and then rotary evaporated to remove dichloromethane to obtain BuTMG, and finally dried in a vacuum oven.

[0031] 2BIM-2Br and BuTMG (molar ratio of 1:2.2) were dissolved in DMSO. Then the mixture was reacted at 50°C for 24 hours, and ether was added dropwise to the solution to precipitate solid. Finally, the solid GBIM was dried in a vacuum oven.

[0032] 0.2 g 6FPBI and 0.002 g GBIM were dissolved in 6 ml DMSO, and then the two solutions were mixed and ultrasonicated for 4 h, and the homogenous mixed solution was cast on a glass plate, and the 6FPBI-X membrane was dried at 80 ° C. The membrane sample was immersed in 85 wt% phosphoric acid at 80 ° C for 12 h to obtain a phosphoric acid-doped membrane.

[0033] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 85.03 mScm -1 The phosphoric acid doping amount was 181.1%. After 120 hours of testing at 160°C, 80.2% of the phosphoric acid remained. The remaining weight after treatment with Fenton's reagent was 74.6% (oxidation stability). After assembling a hydrogen / oxygen single cell, the maximum power density reached 520.8 mW cm-2 .

[0034] Example 2

[0035] The preparation of 6FPBI and GBIM is the same as in Example 1.

[0036] 0.2 g 6FPBI and 0.006 g GBIM were dissolved in 6 ml DMSO, and then the two solutions were mixed and ultrasonicated for 4 h, and the homogenous mixed solution was cast on a glass plate, and the 6FPBI-X membrane was dried at 80 ° C. The membrane sample was immersed in 85 wt% phosphoric acid at 80 ° C for 12 h to obtain a phosphoric acid-doped membrane.

[0037] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 105.26 mScm -1 The phosphoric acid doping amount was 203.6%. After 120h of testing at 160°C, 81.7% of the phosphoric acid remained. The remaining weight after treatment with Fenton's reagent was 79.2% (oxidation stability). After assembling a hydrogen / oxygen single cell, the maximum power density reached 647.1mW cm -2 .

[0038] Example 3

[0039] The preparation of 6FPBI and GBIM is the same as in Example 1.

[0040] 0.2 g 6FPBI and 0.01 g GBIM were dissolved in 6 ml DMSO, and then the two solutions were mixed and ultrasonicated for 4 h, and the homogenous mixed solution was cast on a glass plate, and the 6FPBI-X membrane was dried at 80 ° C. The membrane sample was immersed in 85 wt% phosphoric acid at 80 ° C for 12 h to obtain a phosphoric acid-doped membrane.

[0041] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 127.71 mScm -1 The phosphoric acid doping amount was 247.6%. After 120h of testing at 160°C, 84.0% of the phosphoric acid remained. The remaining weight after treatment with Fenton's reagent was 82.2% (oxidation stability). After assembling a hydrogen / oxygen single cell, the maximum power density reached 507.3mW cm -2 .

[0042] Example 4

[0043] This example is substantially the same as Example 1, except that the molar ratio of 2BIM-2Br to BuTMG is 1:1.5.

[0044] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 78.03 mScm-1 The phosphoric acid doping amount is 172.5%. After 120 hours of testing at 160°C, 79.1% of the phosphoric acid remains. The remaining weight after treatment with Fenton's reagent is 73.8% (oxidation stability).

[0045] Example 5

[0046] This example is substantially the same as Example 1, except that the molar ratio of 2BIM-2Br to BuTMG is 1:1.

[0047] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 74.82 mScm -1 The phosphoric acid doping amount is 167.4%. After 120 hours of testing at 160°C, 77.2% of the phosphoric acid remains. The remaining weight after treatment with Fenton's reagent is 72.9% (oxidation stability).

[0048] Comparative Example 1

[0049] The preparation of 6FPBI is the same as in Example 1.

[0050] 2 g of 6FPBI was dissolved in 6 ml of DMSO and sonicated for 4 hours, the homogenized solution was cast onto a glass plate, and the 6FPBI membrane was dried at 80° C. The membrane sample was immersed in 85 wt % phosphoric acid at 80° C. for 12 hours to obtain a phosphoric acid-doped membrane.

[0051] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 56.61 mScm -1 The phosphoric acid doping amount was 145.3%. After 120h of testing at 160°C, 74.1% of the phosphoric acid remained. The remaining weight after treatment with Fenton's reagent was 71.1% (oxidation stability). After assembling a hydrogen / oxygen single cell, the maximum power density reached 417.6 mW cm -2 .

[0052] Comparative Example 2

[0053] The preparation of 6FPBI and BuTMG is the same as in Example 1.

[0054] 0.2 g 6FPBI and 0.002 g BuTMG were dissolved in 6 ml DMSO, and then the two solutions were mixed and ultrasonicated for 4 hours, and the homogenous mixed solution was cast on a glass plate, and the 6FPBI-X film was dried at 80° C. The film sample was immersed in 85 wt% phosphoric acid at 80° C. for 12 hours to obtain a phosphoric acid-doped film.

[0055] The performance parameters of the exchange membrane test are as follows: the proton conductivity of the membrane at 160°C reaches 87.32 mScm-1 The phosphoric acid doping amount is 187.85%. After 120 hours of testing at 160°C, 76.2% of the phosphoric acid still remains. The remaining weight after treatment with Fenton's reagent is 72.1% (oxidation stability).

[0056] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable technicians familiar with this technology to understand the content of the present invention and implement it accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite proton exchange membrane based on guanidine salt / imidazole derivatives, characterized in that: The structural formula of the composite proton exchange membrane is shown below:

2. A method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 1, characterized in that: The preparation method steps are as follows: (a) Under nitrogen atmosphere, mechanical stirring was used to remove residual air in PPA, DAB and OBBA were completely dissolved in PPA, the temperature was raised to 180°C for reaction for 3 hours, and then the temperature was lowered to 140°C and 6FDA was added until it was completely dissolved, and the temperature was raised to 180°C again for reaction for 3 hours; after the reaction, the solution was poured into deionized water for cooling, the obtained solid was washed with deionized water and neutralized with NaHCO3, and finally, the product was placed in an oven for drying, and the obtained polymer was named 6FPBI; (b) DAB and bromoacetic acid were added to a 5M HCl solution, and the mixture was refluxed for 6 hours under a nitrogen atmosphere. After the reaction was completed, the residual solid was removed by filtration, and the remaining solution was poured into deionized ice water. The solution was neutralized with NaHCO3. As the acidity of the solution decreased, solids gradually precipitated. The obtained solids were washed with deionized water, filtered, and dried in an oven to obtain 2BIM-2Br; (c) TMG was dissolved in acetonitrile under nitrogen atmosphere, and then n-butyl bromide was added dropwise to the solution under ice bath condition. After the addition was complete, the ice bath was removed and the reaction was carried out at room temperature for 24 hours. After the reaction was completed, a 20 wt % NaOH aqueous solution was added dropwise to the flask under ice bath condition, and then extracted with dichloromethane. After drying, dichloromethane was removed by rotary evaporation to obtain BuTMG, and finally dried in a vacuum oven; (d) 2BIM-2Br and BuTMG were dissolved in DMSO and then reacted at 50°C for 24 hours. Ether was added dropwise to the solution to precipitate solids. The obtained solid GBIM was dried in a vacuum oven. (e) Preparation of composite membrane and phosphoric acid doping 6FPBI and GBIM were dissolved in DMSO respectively, and then the two solutions were mixed and ultrasonically treated for 4 hours. The homogenous mixed solution was cast onto a glass plate and dried at 80°C. The membrane sample was immersed in 85wt% phosphoric acid at 80°C for 12 hours to obtain a phosphoric acid-doped membrane.

3. The method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 2, characterized in that: In step (a), the molar ratio of DAB, OBBA and 6FDA is 1:0.5:0.5, and the amount of polyphosphoric acid used is greater than 10 times the total mass of the monomers.

4. The method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 2, characterized in that: In step (b), the molar ratio of DAB to bromoacetic acid is 1:2.

2.

5. The method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 2, characterized in that: In step (c), the molar ratio of TMG to n-butyl bromide is 1:1.

1.

6. The method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 2, characterized in that: In step (d), the molar ratio of 2BIM-2Br to BuTMG is 1:1-2.

2.

7. The method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 2, characterized in that: In step (d), the structural formula of GBIM is shown below:

8. The method for preparing a composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 2, characterized in that: In step (e), the mass of GBIM accounts for 1-5% of the mass of 6FPBI.

9. An application of the composite proton exchange membrane based on guanidine salt / imidazole derivatives according to claim 1, characterized in that: The proton exchange composite membrane is applied to the proton exchange membrane of a high-temperature fuel cell.